1999
DOI: 10.1038/sj.bjp.0702541
|View full text |Cite
|
Sign up to set email alerts
|

In vitroα1‐adrenoceptor pharmacology of Ro 70–0004 and RS‐100329, novel α1A‐adrenoceptor selective antagonists

Abstract: Bank, She eld, ST10 2TN and 4 8 Palace Garden, Royston, Hertfordshire, S68 5AD1 It has been hypothesized that in patients with benign prostatic hyperplasia, selective antagonism of the a 1A -adrenoceptor-mediated contraction of lower urinary tract tissues may, via a selective relief of outlet obstruction, lead to an improvement in symptoms. 2 The present study describes the a 1 -adrenoceptor (a 1 -AR) subtype selectivities of two novel a 1 -AR antagonists, Ro 70-0004 (aka RS-100975) and a structurally-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 25 publications
5
54
0
Order By: Relevance
“…This hypothesis was supported by results obtained in SHR, in which fiduxosin was less hypotensive than other agents on a mole per kilogram basis, and also elicited weaker, more transient effects in a postural hypotension challenge. Similar results have been reported with the ␣ 1a -selective compounds Ro-70-0004 (Williams et al, 1999), RWJ-38063, and RWJ-69736 (Pulito et al, 2000), supporting the importance of ␣ 1b -adrenoceptors for cardiovascular function as suggested by data with knockout mice lacking the ␣ 1b -adrenoceptor gene (Cavalli et al, 1997). Recently, a novel compound has been described, B8805-033 (Eltze et al, 2001), with chemical and pharmacological similarities to 5-methyl-urapidil and flesinoxan.…”
Section: Discussionsupporting
confidence: 75%
“…This hypothesis was supported by results obtained in SHR, in which fiduxosin was less hypotensive than other agents on a mole per kilogram basis, and also elicited weaker, more transient effects in a postural hypotension challenge. Similar results have been reported with the ␣ 1a -selective compounds Ro-70-0004 (Williams et al, 1999), RWJ-38063, and RWJ-69736 (Pulito et al, 2000), supporting the importance of ␣ 1b -adrenoceptors for cardiovascular function as suggested by data with knockout mice lacking the ␣ 1b -adrenoceptor gene (Cavalli et al, 1997). Recently, a novel compound has been described, B8805-033 (Eltze et al, 2001), with chemical and pharmacological similarities to 5-methyl-urapidil and flesinoxan.…”
Section: Discussionsupporting
confidence: 75%
“…In the cavernous artery, pharmacological analysis of these antagonists was clearcut. RS 100329, selective for the a 1A -AR subtype (Williams et al, 1999), inhibited PE responses potently and competitively. The high potency and Schild compliance of RS 100329 indicated that there is no need to invoke participation from other a 1 -AR subtypes.…”
Section: Discussionmentioning
confidence: 97%
“…RS 100329 has been shown to be a potent antagonist at a 1A -ARs with a pA 2 /pK B of between 9.2 and 9.6 (Williams et al, 1999;Choppin et al, 2001;Cleary et al, 2003). Pre-incubation with 100 nM RS 100329 caused no further rightward movement of the PE response in dorsal arteries, and a pK B of 9.0370.07 (n ¼ 6) was determined from 1 and 10 nM antagonist data.…”
Section: Agonist Profilesmentioning
confidence: 97%
“…and demonstrates a 126-and 50-fold selectivity over α 1B and α 1D -adrenoceptor subtypes, 19,20 thus at the concentration used in the present study (10nM) it would only have an action at α 1A -adrenoceptors. The lack of involvement of α 1D -adrenoceptors was confirmed using BMY7378, an antagonist with a greater than 100-fold high affinity for the α 1D -adrenoceptor subtype over α 1A and α 1B -adrenoceptors.…”
Section: α-Adrenoceptorsmentioning
confidence: 99%